New barley genotypes identified with superior forage, grain and biomass production after cutting - CGIAR Research Program on Livestock (2019)
Nine varieties were identified in a field trial as having superior forage production and regrowth (grain and biomass production after cutting) and are under second year field trial. 28 new genotypes selected in 2019 based on superior early vigor and fodder production are under first year testing.